1998
DOI: 10.1021/je980167w
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Anthracene in Ternary Propanol + Butanol + 2,2,4-Trimethylpentane Solvent Mixtures

Abstract: Experimental solubilities are reported for anthracene dissolved in ternary 1-propanol + 1-butanol + 2,2,4-trimethylpentane, 1-propanol + 2-butanol + 2,2,4-trimethylpentane, 2-propanol + 1-butanol + 2,2,4-trimethylpentane, and 2-propanol + 2-butanol + 2,2,4-trimethylpentane solvent mixtures at 25°C. Nineteen compositions were studied for each of the four solvent systems. Results of these measurements are used to test the predictive ability of the ternary solvent form of the combined NIMS/Redlich-Kister equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 6 publications
0
30
4
Order By: Relevance
“…In the case of structurally similar drug molecules, the numerical values of the S i coefficients were found to be nearly constant in a given binary solvent mixture. 10 More recently, Deng et al [11][12][13] and Pribyla et al [14][15][16] have shown that the S i coefficients determined by regressing experimental anthracene data in binary alkane + alkane, alkane + alcohol, alcohol + alcohol, alcohol + ether, and alkane + ether solvent mixtures allow one to predict anthracene solubilities in ternary alkane + alkane + alcohol, alkane + alcohol + alcohol, and alkane + alcohol + ether solvent mixtures. The predictive expression for the ternary solvent mixture is a mole fraction average of the logarithmic solute solubilities in the three pure solvents [(x A sat ) B , (x A sat ) C , and (x A sat ) D ] plus a Redlich-Kister summation term for each solvent pair.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of structurally similar drug molecules, the numerical values of the S i coefficients were found to be nearly constant in a given binary solvent mixture. 10 More recently, Deng et al [11][12][13] and Pribyla et al [14][15][16] have shown that the S i coefficients determined by regressing experimental anthracene data in binary alkane + alkane, alkane + alcohol, alcohol + alcohol, alcohol + ether, and alkane + ether solvent mixtures allow one to predict anthracene solubilities in ternary alkane + alkane + alcohol, alkane + alcohol + alcohol, and alkane + alcohol + ether solvent mixtures. The predictive expression for the ternary solvent mixture is a mole fraction average of the logarithmic solute solubilities in the three pure solvents [(x A sat ) B , (x A sat ) C , and (x A sat ) D ] plus a Redlich-Kister summation term for each solvent pair.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of structurally similar drug molecules, the numerical values of the S i coefficients were found to be nearly constant in a given binary solvent mixture. 10 More recently, Deng et al [11][12][13] and Pribyla et al [14][15][16] have shown that the S i coefficients determined by regressing experimental anthracene data in binary alkane + alkane, alkane + alcohol, alcohol + alcohol, alcohol + ether, and alkane + ether solvent mixtures allows one to predict anthracene solubilities in ternary alkane + alkane + alcohol, alkane + alcohol + alcohol, and alkane + alcohol + ether solvent mixtures. The predictive expression for the ternary solvent mixture is a mole fraction average of the logarithmic solute solubilities in the three pure solvents [(x A sat ) B , (x A sat ) C , and (x A sat ) D ] plus a Redlich-Kister summation term for each solvent pair.…”
Section: Resultsmentioning
confidence: 99%
“…Equation 1 has been shown to provide very accurate mathematical representations of anthracene, pyrene, and carbazole solubilities in a large number of both complexing and noncomplexing solvent mixtures. [1][2][3] For a ternary solvent system, the mathematical representation takes the form Recent studies have shown that eq 2 provides reasonably accurate predictions for anthracene solubilities in ternary two alkane + alcohol 10,11 and alkane + two alcohol [12][13][14] * To whom correspondence should be addressed. E-mail: acree@unt.edu.…”
Section: Resultsmentioning
confidence: 99%